How to invest in the “Market of Sustainability”: evaluating the impacts of a real estate investment across ESG criteria [Investire nel “Mercato sostenibile”: Valutare gli impatti di un investimento immobiliare attraverso i criteri ESG] - Cadamuro Morgante, Federica; Gholamzadehmir, Maryam; Sdino, Leopoldo; Rosasco, Paolo (Valori e valutazioni, 2023)
This article is based on recent research and debates on the development and investment models of the Real Estate sector encouraged by the new policies and action programs of the European Union, and primarily the seventeen Sustainable Development Goals-SDGs of the 2030 Agenda. In particular, the research emphasizes evaluating the effects of Italian Residential Real Estate investments on the three dimensions of sustainability conceptualized through the ESG – Environmental Social Governance criteria. In this context, the authors experiment with identifying a set of indicators according to ESG criteria helpful in describing the incidence of activities in Real Estate processes (along the entire life cycle of the asset) and, therefore, to guide residential market investors in choices with a high sustainable impact. The methodology of this work has firstly identified the European and Italian regulatory framework relating to the ESG sphere by studying the indicators already in use or developed for measuring sustainable performance particularly for real estate sector, like gaps in literature about proper methodologies to measure performance while involving process’ actors. Then, the proposed participatory methodology has been built by taking as reference a real case study – reuse of a building complex in the city of Milan for residential purposes- to identify with a panel of experts and involved actors the phases and sub-phases listed as work-breakdown structure, which may be subject to performance and impact measurement. Furthermore, ESG impacts in terms of beneficiaries from the project and key performance indicators has been assessed and ranked, resulting in an economic and social sustainability criteria priority in involved actors’ sake. Therefore, this research work provides the foundations for a replicable evaluation system for measuring sustainability standards in the residential Real Estate market considering innovatively co-participative decision-making processes along the project life-cycle. However, the methodology can be reinforced in the future with sensitivity methods on involved actors’ primary choices in the multi-criteria process and the enlargement of Panel experts’ profiles or, even, addressed to other targets more than the residential one. Il presente articolo si ispira a recenti ricerche e studi sui modelli di investimento nel settore immobiliare promossi dalle nuove politiche e dai programmi d’azione dell’Unione Europea e, principalmente, dai diciassette Obiettivi di Sviluppo Sostenibile – OSS – dell’Agenda 2030. In particolare, la ricerca si concentra sulla valutazione della sostenibilità delle scelte progettuali secondo le tre dimensioni (ambientale, economica e sociale) concettualizzate nei criteri ESG – Environmental Social Governance. In questo contesto, gli autori sperimentano l’identificazione di un set di indicatori derivati dai criteri ESG utili agli operatori del mercato immobiliare nella scelta di soluzioni progettuali sostenibili. In una prima fase lo studio ha analizzato il quadro normativo europeo e italiano relativo ai criteri ESG, analizzando quali sono gli indicatori definiti per la misurazione delle performance di sostenibilità e come questi si possono applicare in ambito immobiliare. Successivamente, prendendo a riferimento un caso di studio reale relativo al recupero – a fini residenziali – di un complesso edilizio a Milano – è stato selezionato un Panel di esperti e di attori coinvolti nel progetto al quale è stato chiesto di indicare quali sono gli aspetti e i criteri significativi per operare scelte sostenibili e di determinarne l’importanza (peso). L’obiettivo è quello di definire un sistema di valutazione della sostenibilità degli interventi in ambito immobiliare, con particolare riferimento al segmento residenziale, considerando gli effetti generati dalle scelte progettuali lungo tutto il ciclo di vita del progetto, dalla fase di ideazione a quella di costruzione e gestione. I risultati ottenuti evidenziano che gli aspetti di sostenibilità maggiormente significativi sono quelli legati alla sostenibilità economica e al benessere degli utenti e dei fruitori dell’intervento; l’applicabilità della metodologia – e la significatività dei risultati – dovranno essere ulteriormente verificati attraverso l’ampliamento dei profili dei componenti del Panel di esperti e la sperimentazione su altre tipologie di intervento e di destinazioni d’uso.